Advanced Extremely Durable 3D Bifunctional Air Electrodes for Rechargeable Zinc‐Air Batteries. Issue 6 (4th December 2013) - Lee, Dong Un; Choi, Ja‐Yeon; Feng, Kun; Park, Hey Woong; Chen, Zhongwei
<x xml:space="preserve">Abstract</x> A very practical, 3D air electrode architecture based on a bifunctional cobalt oxide nanowire array that is active towards both the oxygen reduction and oxygen evolution reactions is introduced. This advanced carbon‐ and binder‐free electrode exhibits remarkable electrochemical durability, with 600 h of operation under ambient conditions in a rechargeable zinc‐air battery. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>